Legal Protection for Victims of Sexual Slavery as a War Crime in Russia and Ukraine - Gabryella, Gabryella (Universitas Negeri Surabaya, 2024)
This research discusses the legal protection of victims of sexual slavery as a war crime in Russia and Ukraine. The conflict between Russia and Ukraine has resulted in significant violations of international humanitarian law, including sexual violence committed by Russian soldiers. This research explores the legal implications of sexual slavery as a war crime in the context of the ongoing conflict. In this study, the author uses a socio-legal approach to analyze the legal protection of victims of sexual slavery. The results show that the crime of sexual slavery as a war crime in Russia and Ukraine can be understood through the lens of international human rights law. This paper hopes to contribute to the development of human rights law and the protection of victims of sexual slavery as a war crime.